The Effectiveness of the Quantum Learning Model in Improving Students' Speaking Skills at SMKN 1 Palopo - Aliyah Warda; Rahmawati Upa'; Andi Mangnguntungi Sudirman (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This study investigated the effectiveness of the Quantum Learning model in improving eleventh-grade students' speaking skills at SMKN 1 Palopo. The research used a quantitative pre-experimental design involving one group that received a pre-test, four treatment meetings, and a post-test. The population consisted of 527 students, while the sample comprised 29 students of class XI AKL 3 selected through random sampling. The research instrument was an oral speaking test assessed through three indicators: pronunciation, comprehension, and fluency. During the treatment, the Quantum Learning model was implemented through the TANDUR framework: Grow, Experience, Name, Demonstrate, Repeat, and Celebrate. Learning activities focused on descriptive text, particularly describing tourist attractions and performing as a tour guide. The data were analyzed using descriptive statistics, normality testing, and a paired sample t-test with SPSS version 26. The results showed that the students' mean score increased from 44.69 in the pre-test to 61.79 in the post-test. The paired sample t-test showed a mean difference of -17.103, t = -4.816, df = 28, and Sig. (2-tailed) = 0.000, which was lower than 0.05. These findings indicate a significant improvement in students' speaking skills after the implementation of the Quantum Learning model. The treatment also encouraged students to become more confident, focused, creative, and active in speaking activities. Therefore, the Quantum Learning model can be considered an effective alternative for improving students' speaking skills in English language learning.